2005
DOI: 10.1063/1.2032614
|View full text |Cite
|
Sign up to set email alerts
|

The effect of TiO2 doping on the structure and magnetic and magnetotransport properties of La0.75Sr0.25MnO3 composite

Abstract: The effect of TiO2 doping on the structure and magnetic and magnetotransport properties of La0.75Sr0.25MnO3 (LSMO)∕xTiO2 has been investigated. These studies show that at low doping level (x⩽2) TiO2 mainly goes into the grain-boundary region, but at high doping level (x⩾3), some part of the TiO2 goes into the perovskite lattice substituting Mn in LSMO and the remainder segregates as a separate phase at the grain boundaries. Results also show that the TiO2 doping has an important effect on a low-field magnetore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…Several attempts have been made to enhance the LFMR effect of perovskite manganites by mixture of these CMR materials with secondary phases. They include LSMO/CeO 2 [15], LCMO/ZnO [16], LSMO/Al 2 O 3 [17] and LSMO/TiO 2 [18]. Also Coey et al [19] showed that by doping of half metallic ferromagnet CrO 2 with insulating antiferromagnetic Cr 2 O 3 enhances the LFMR.…”
Section: Introductionmentioning
confidence: 98%
“…Several attempts have been made to enhance the LFMR effect of perovskite manganites by mixture of these CMR materials with secondary phases. They include LSMO/CeO 2 [15], LCMO/ZnO [16], LSMO/Al 2 O 3 [17] and LSMO/TiO 2 [18]. Also Coey et al [19] showed that by doping of half metallic ferromagnet CrO 2 with insulating antiferromagnetic Cr 2 O 3 enhances the LFMR.…”
Section: Introductionmentioning
confidence: 98%
“…The application of moderate magnetic field can align the originally disordered Mn spins, thus reducing the scattering and leading to a LFMR. Several attempts have been made to enhance the LFMR effect of perovskite manganites: (1) making composites of these CMR materials with secondary phases [11][12][13][14][15] and (2) making powder compacts of materials with spin polarized charge carriers [16][17][18][19]. In the latter, the MR can be optimized by the adjustment of the microstructural characteristics, such as grain size.…”
Section: Introductionmentioning
confidence: 99%
“…Guinea [10] discussed the role of tunneling via paramagnetic impurity states in the grain boundary barrier. Several attempts have been made to enhance the LFMR effect of perovskite manganites by mixing these CMR materials with insulating second oxide and polymer phases [15][16][17][18][19][20]. Although the doping effects of nonmagnetic impurities on electrical transport of manganites have been investigated by several groups, the magnetic and magnetotransport behaviors of composites of magnetic insulator and CMR materials have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%